Mapping Mass Customization - Brandão, Filipe J.S.; Paio, A. (ShoCK! - Sharing Computational Knowledge!, 2017)
Mass customization (MC) and personal fabrication (PF) are current relevant topics in architecture offices practice and schools design research. Architects are adopting information based design and production techniques as a response to architectural century challenges. However, is not clear how various authors used and transformed the concept in practice, research and industry after three decades since the MC term was introduced by Davis (1987). Therefore, is essential to map the most relevant works in the field in relation to production and design control. The paper presents some of the results of the ongoing study through an evolving map that aims to visualize relationships, layering complexity and revealing difference.